Cross-cultural adaptation, validity, and reliability of the Indonesian version of the Hill-Bone high blood pressure therapy compliance scale - Eldawati, Eldawati; Said, Faridah Mohd; Umar, Nur Syazana (International Journal of Public Health Science (IJPHS), 2025)
Hypertension is a long-term condition that enables individuals to take an active role in managing their health care— inadequate adherence to medication regimens is a major factor contributing to treatment failure. We translated and updated the Hill-Bone high blood pressure therapy compliance scale for use in Indonesia, where systemic hypertension is becoming increasingly prevalent.  This study aims to evaluate the validity and reliability of the Indonesian version of the Hill-Bone high blood pressure therapy compliance scale. The descriptive cross-sectional research was conducted in East Java, Indonesia, during June and July 2021. For the purpose of selecting 144 persons who had hypertension, a convenience sample was utilized. The Hill-Bone high blood pressure therapy compliance instrument was translated from English into Indonesian using a forward-backward translation method, followed by evaluation by an expert panel and pilot testing. To assess its reliability, the Cronbach's alpha coefficient and item-total correlation were utilized. A Kaiser-Meyer-Olkin (KMO) value of 0.945 confirmed the adequacy of the sample for the study. Additionally, the Bartlett’s test yielded a significant result (X² = 132.41; p < 0.001), supporting the appropriateness of conducting a factor analysis. Using factor analysis, the Hill-Bone high blood pressure therapy compliance scale revealed a single factor with an eigenvalue >1 that explained 42.13% of the total variation. The Cronbach alpha coefficient of the Hill-Bone high blood pressure therapy compliance scale was 0.901. The Hill-Bone high blood pressure therapy compliance instrument has been successfully translated and tailored for the Indonesian population, with consideration of their cultural context. In order to provide an accurate prediction regarding the impact that this intervention would have on patients' adherence, the Hill-Bone high blood pressure therapy compliance scale could be of assistance.